Anti-flagellin IgY antibodies protect against Pseudomonas aeruginosa infection in both acute pneumonia and burn wound murine models in a non-type-specific mode. (August 2021) - Ahmadi, Tooba Sadat; Mousavi Gargari, Seyed Latif; Talei, Daryush
Graphical abstract: Highlights: Anti-flagellin IgY antibodies protect P. aeruginosa infected burned mice. Anti-flagellin IgY antibodies protect against PA infection in acute pneumonia. The IgY immune response induced against PA flagellins is not type-specific. Immunotherapy with anti-FlaA-IgY caused ADE of infection in burn wound model. Abstract: Pseudomonas aeruginosa (PA) is one of the most dominant causes of nosocomial infections in burn patients. Increasing emergence of antibiotic-resistant strains highlights the need for novel antimicrobial agents. Flagellin, the main component protein of flagellum, is determined as the major antigen interacting with anti- P. aeruginosa IgY antibodies. The current study was aimed to evaluate the antibacterial potency of IgY antibodies raised against recombinant type A, and B flagellins. The immunogenicity and specificity of IgY antibodies were confirmed through indirect ELISA and western blot analysis, respectively. Anti-flagellin IgYs reduced the motility, biofilm formation and invasion potency of both strains. The cell surface hydrophobicity (CSH) of bacteria was increased upon IgY treatment, and in vitro opsonophagocytosis assay confirmed the high protective potency of specific antibodies via polymorphonuclear leukocyte (PMN)-augmented bacterial cell killing. The protective efficacy of IgYs was also studied in both acute pneumonia and burn wound murine models. Anti-flagellin B-IgY induced 100 % and 40 % protection against laboratory, and hospital strains in burn wound model, respectively. Protection in acute pneumonia against all strains was 100 %. Anti-flagellin A-IgY failed to protect mice in burn wound model, but provided 100 % protection against all strains in acute pneumonia challenge. In vitro, ex vivo and in vivo experiments confirmed the dose-dependent and non-type specific essence of anti-flagellin IgY antibodies, providing the benefit of covering all strain types in a dose dependent manner. Our findings provide evidence that anti-flagellin IgY antibodies qualify as novel economical therapeutic option against PA infection.